Environmental management system and cleaner production (John Wiley & Sons, 1996)
Environmental Management Systems (EMSs) are a way in which business and industry can implement a system of self-regulation on their processes, in order to aid the promotion of clean technology. This book brings together wide ranging analysis and practical experience on Environmental Management Systems and Cleaner Production. This highlights the importance of a clear understanding of complex environmental issues and the relative impact of business and industry, linked to national and international standards and regulations, in developing an efficient Environmental Management System.